Environmental Impact Assessment: A Tool for Sustainable Development (International Journal of Innovative Research in Computer Science & Technology, 2020)
The planet is divided between people who  are alive and those who are deceased. However, a sizable  portion belongs to people who have not yet been born.  Anticipatory and participative development techniques are  necessary for informed decision-making on the best use of  natural resources and sustainable development to ensure  that development and environmental health go hand in  hand. One of these tools is the environmental impact  assessment (EIA). This essay aims to define the idea of  environmental impact assessment (EIA) and analyse its  numerous components, including its basic ideals, guiding  principles, shortcomings, and recommendations for  improvement.
Keywords: Development; Sustainable Development; Environmental Impact Assessment.